Impact of health science popularization videos on user perceived value and continuous usage intention: based on the C-A-C and ECM model framework - Xuan, Wenxia; Phongsatha, Thanawan; Hao, Lijie; Tian, Kun (Frontiers in Public Health, 2024)
Objective: To enhance individuals' sustained intention to use health science popularization videos, this study investigated the path relationships and influencing mechanisms of health science popularization video factors on users' perceived value, expectancy confirmation, enjoyment, satisfaction, trust, and continuous usage intention based on the cognitive-affective-conative and expectation-confirmation model theoretical framework.Methods: This study adopted a cross-sectional design and collected data using selfadministered questionnaires. The hypotheses were analyzed using the smart partial least squares (Smart-PLS) structural equation modeling method with a dataset containing 503 valid responses. Subsequently, comprehensive data analysis was conducted.Results: Blogger and video quality factors present in health science popularization videos substantially influenced users' perceived value(p < 0.001). Furthermore, users' expectancy confirmation exerted a positive influence on both users' perceived value (P < 0.001) and satisfaction(P < 0.01). Perceived value, in turn, positively impacted satisfaction(P < 0.001) and pleasure (P < 0.001). User satisfaction (P < 0.001) and pleasure (P < 0.001) directly enhanced trust, which, in turn, significantly and directly impacted continuous usage intention (P < 0.001).Discussion: This study offers both theoretical and practical insights into enhancing the quality of health science popularization videos. From a theoretical perspective, it expands upon the cognitive-affective-conative and expectation-confirmation model theoretical frameworks, enriches the theoretical model, and offers theoretical references for future research in this domain. From a practical perspective, enhancing the overall quality of health science popularization content significantly influences users' perceived value, emotional engagement, and continued usage intention to engage with the content.